Pengaruh Pengalaman Wisatawan, Kualitas Layanan dan Daya Tarik Wisata terhadap Niat Berkunjung Kembali di Desa Ekowisata Pancoh - Atika Fauziana; Guruh Ghifar Zalzalah (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to determine the influence of tourist experience, service quality, and tourist attractions on revisit intention in Pancoh Ecotourism Village. This village is one of the developing ecotourism-based tourist destinations in the Special Region of Yogyakarta and attracts tourists through its unique nature and local culture. The research sample consisted of 100 respondents selected using a non-probability sampling technique with a purposive sampling approach, namely tourists who have visited Pancoh Ecotourism Village. Data collection was carried out by distributing questionnaires, then analyzed using the partial least squares structural equation modeling (SEM-PLS) method with the WarpPLS application version 8.0 to test the relationship between variables. The results showed that the variables of service quality and tourist attractions have a positive and significant effect on revisit intention. This indicates that improving service quality, such as friendliness, accuracy, and comfort, as well as the development of tourist attractions in the form of natural beauty, local culture, and supporting facilities can encourage tourists to revisit. However, the variable of tourist experience did not have a significant effect on revisit intention, which means that individual experience is not yet a major determining factor in influencing tourist decisions. These findings emphasize the importance of a destination management strategy that focuses on improving the quality of services and tourist attractions to strengthen the sustainability of Pancoh Ecotourism Village.